Pemberdayaan Perangkat Desa Silo Baru Melalui Pelatihan Teknologi Informasi Untuk Meningkatkan Efektivitas Administrasi Desa - Ramdhan, William; Santoso, Santoso; Nofriadi, Nofriadi; Kartika, Juli (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Efficient and transparent administration management is a primary requirement in village governance in the digital era. This community service activity was carried out with the aim of empowering the Silo Baru Village apparatus, Silau Laut District, through training in the use of information technology, especially the use of Microsoft Office applications (Word, Excel, and PowerPoint). This training is designed to increase the capacity of village apparatus in compiling administrative documents, managing data, and presenting information effectively and systematically. The implementation method includes a participatory approach with a combination of material delivery, direct practice, and intensive mentoring. The results of the activity showed an increase in the skills of village apparatus in operating office applications independently, which had a positive impact on work efficiency, data management accuracy, and transparency of administrative services. This program is expected to be the first step in encouraging the digitalization of village government towards more modern and accountable governance.Keywords: Village Administration; Village Apparatus; Information Technology; Microsoft Office; Digitalization of Government  Abstrak: Pengelolaan administrasi yang efisien dan transparan menjadi tuntutan utama dalam tata kelola pemerintahan desa di era digital. Kegiatan pengabdian masyarakat ini dilaksanakan dengan tujuan untuk memberdayakan perangkat Desa Silo Baru, Kecamatan Silau Laut Kabupaten Asahan, melalui pelatihan pemanfaatan teknologi infomasi, khususnya penggunaan aplikasi Microsoft Office (Word, Excel, dan PowerPoint). Pelatihan ini dirancang untuk meningkatkan kapasitas perangkat desa dalam menyusun dokumen administrasi, mengelola data, serta menyajikan informasi secara efektif dan sistematis. Metode pelaksanaan meliputi pendekatan partisipatif dengan kombinasi penyampaian materi, praktik langsung, dan pendampingan intensif. Hasil kegiatan menunjukkan peningkatan keterampilan perangkat desa dalam mengoperasikan aplikasi perkantoran secara mandiri, yang berdampak positif terhadap efisiensi kerja, akurasi pengelolaan data, serta transparansi layanan administrasi. Program ini diharapkan menjadi langkah awal dalam mendorong digitalisasi pemerintahan desa menuju tata kelola yang lebih modern dan akuntabel.Kata kunci: Administrasi Desa; Perangkat desa; Teknologi informasi; Microsoft Office; Digitalisasi Pemerintahan